Planar square multiband frequency reconfigurable microstrip fed antenna with quadratic Koch‐Island fractal slot for wireless devices. Issue 1 (18th November 2014) - Trad, Imen Ben; Rmili, Hatem; Floch, Jean Marie; Zouch, Wassim; Drissi, Mohamed
ABSTRACT A planarprinted multiband microstrip fed antenna with reconfigurable frequency performance was designed for multistandard wireless communication systems. The antenna consists on a square shaped patch with an optimized centered Koch‐Island fractal slot. The antenna allows a reconfigurability of the frequency bands by incorporating 16 PIN diodes inside the fractal slot which is highly complex. That is why short and open circuits will be used to produce frequency agility instead of RF switches (for proof of the concept). The proposed antenna is capable to switch between 15 operating frequency bands centered at 1.7, 1.77, 2.36, 2.43, 3.30, 3.61, 3.67, 3.79, 4.05, 4.34, 4.59, 5.2, 5.27, 5.47, and 5.57 GHz through four operating modes M1–M4 over the wide range 1–6 GHz. Prototypes corresponding to different modes were manufactured and characterized. Simulated and measured results are presented and discussed. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:207–212, 2015